Comparative Histological and Histomorphometric Results of Six Biomaterials Used in Two-Stage Maxillary Sinus Augmentation Model after 6-Month Healing. (27th June 2018) - La Monaca, Gerardo; Iezzi, Giovanna; Cristalli, Maria Paola; Pranno, Nicola; Sfasciotti, Gian Luca; Vozza, Iole
Abstract : Objectives . To evaluate the performances of six different bone substitute materials used as graft in maxillary sinus augmentation by means of histological and histomorphometric analysis of bone biopsies retrieved from human subjects after a 6-month healing period. Materials and Methods . Six consecutive patients (3 males, 3 females, aged 50-72 years), healthy, nonsmokers, and with good oral hygiene, presenting edentulous posterior maxilla with a residual bone crest measuring ≤ 4 mm in vertical height and 3 to 5 mm in horizontal thickness at radiographic examination, were selected to receive sinus augmentation and delayed implant placement. Under randomized conditions, sinus augmentation procedures were carried out using mineralized solvent-dehydrated bone allograft (MCBA), freeze-dried mineralized bone allograft (FDBA), anorganic bovine bone (ABB), equine-derived bone (EB), synthetic micro-macroporous biphasic calcium-phosphate block consisting of 70% beta-tricalcium phosphate and 30% hydroxyapatite (HA- β -TCP 30/70), or bioapatite-collagen (BC). After 6 months, bone core biopsies were retrieved and 13 implants were placed. Bone samples were processed for histological and histomorphometric analysis. CT scans were taken before and after surgery. After 4 months of healing, patients were restored with a provisional fixed acrylic resin prosthesis, as well as after further 2-4 months with a definitive cemented zirconia or porcelain-fused-to-metal crowns. Results . There were no postoperative complications or implant failures. The histological examination showed that all biomaterials were in close contact with newly formed bone, surrounding the graft granules with a bridge-like network. No signs of acute inflammation were observed. The histomorphometry revealed 20.1% newly formed bone for MCBA, 32.1% for FDBA, 16.1% for ABB, 22.8% for EB, 20.3% for HA- β -TCP 30/70, and 21.4% for BC. Conclusions . Within the limitations of the present investigation, all the six tested biomaterials showed good biocompatibility and osteoconductive properties when used in sinus augmentation procedures, although the FDBA seemed to have a better histomorphometric result in terms of newly formed bone and residual graft material. This trial is registered with ClinicalTrials.gov Identifier (Registration Number):NCT03496688 .